IMPLEMENTATION OF THE GAMIFICATION-BASED TGT LEARNING MODEL TO OPTIMIZE LEARNING OUTCOMES OF GRADE IV STUDENTS - slahstisyifa dien dewi safitri (Teaching and General Education Studies, 2026)
The low interest of elementary school students in Natural Science (IPA) indicates the need for a more engaging and interactive learning approach. Traditional teaching methods often fail to stimulate active student participation; therefore, innovative strategies such as the Team Games Tournament (TGT) learning model are required. This study aims to determine the effectiveness of the gamification-based TGT learning model in improving fourth-grade students’ science learning outcomes. The research employed a quantitative approach using a pre-experimental design with a One-Group Pretest–Posttest format. The study was conducted at SD Negeri Kertosari and involved 18 Grade IV students. Data were collected through learning outcome tests, observations, and documentation. The TGT model was implemented in a single treatment session using science material on the topic of “Energy.” The results revealed a significant improvement in students’ learning outcomes, as the average score increased from 45.00 in the pretest to 85.00 in the posttest. In conclusion, the gamification-based TGT learning model is effective in enhancing students’ understanding and learning outcomes in natural science at the elementary school level. This study implies that incorporating competitive and game-based elements into cooperative learning can increase student engagement and achievement. Future research is recommended to integrate TGT with digital learning media and to examine its effectiveness across different subjects and grade levels.